Development of higher order thinking skills questions on kahoot media in Islamic religious education and character education - Saputri, Rikhel (Program Studi Pendidikan Agama Islam STAI Auliaurrasyidin Tembilahan, 2025)
This study develops valid, practical, and potentially effective Higher Order Thinking Skills (HOTS) questions using Kahoot media for Islamic Religious Education and Character Education (PAI and BP). The research employed Design Research with a development study approach, consisting of two stages: preliminary (analysis and design) and prototyping (expert review, one-to-one, small group, and field test). Data were collected through documentation, walkthroughs, questionnaires, and tests. The study produced 20 multiple-choice HOTS questions validated in terms of content, construct, and language by expert validators. Item validity was confirmed through SPSS analysis, showing r_count > r_table (0.361). Practicality was demonstrated through small group trials with a score of 4.04, categorized as practical. Potential effectiveness was evidenced by field test results with an average student score of 72.55, categorized as good. The Kahoot-based HOTS questions successfully engaged students in interactive learning while developing analytical and evaluative thinking skills aligned with the Merdeka Curriculum learning outcomes for Shu'abul Iman material.